(untitled) (Research, Society and Development, 2022)
Objective: To map the scientific evidence available in the current literature that includes characteristics of nursing care for newborns in intensive care undergoing epicutaneous catheterization assisted by bedside ultrasound. Methodology: Scoping review protocol, carried out in compliance with the Joanna Briggs Institute methodology and the checklist of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. The research question is: what are the characteristics of nursing care for critically ill newborns submitted to epicutaneous catheterization assisted by bedside ultrasound- described in recent literature? Searches for articles will be carried out in five databases and in Google Scholar, which, as it indexes the so-called “gray literature”, will also be accessed to capture theses and dissertations. The analysis of citations will be another resource to expand the sample, which will be composed of research published in the last five years, which adhere to the subject studied. The entire selection flow will be presented as per the new version of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: The results of the scoping review will enable the stratification of nurses’ care for newborns submitted to epicutaneous catheterization assisted by bedside ultrasound in neonatal units. Final considerations: This study constitutes the first phase in a research agenda that aims to build an analytical matrix based of sensitive indicators for the care provided by nurses to neonates undergoing epicutaneous catheterization with the aid of portable bedside ultrasound. Open Science Framework Registration: DOI: 10.31219/osf.10/jh7f9.